Endoscopic Perspective in Cholangiocarcinoma Diagnostic Process. (20th December 2019) - Urban, O.; Vanek, P.; Zoundjiekpon, V.; Falt, P.
Abstract : Cholangiocarcinoma is a malignancy arising from the epithelial lining of the intrahepatic or extrahepatic biliary tract. Timely diagnosis is challenging due to its silent clinical course. As reliable laboratory markers are lacking, diagnostic imaging plays a pivotal role. While cross-sectional imaging studies are usually conclusive for intrahepatic lesions, endoscopy plays an essential role in cases of extrahepatic tumors. Rational utilization of different diagnostic methods based on available evidence is needed. This article focuses on the diagnostic role of advanced biliary endoscopy, including endoscopic retrograde cholangiopancreatography, cholangioscopy, endoscopic ultrasonography, and intraductal sonography.